14-(4m+5)=4+3m-16

Simple and best practice solution for 14-(4m+5)=4+3m-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-(4m+5)=4+3m-16 equation:


Simplifying
14 + -1(4m + 5) = 4 + 3m + -16

Reorder the terms:
14 + -1(5 + 4m) = 4 + 3m + -16
14 + (5 * -1 + 4m * -1) = 4 + 3m + -16
14 + (-5 + -4m) = 4 + 3m + -16

Combine like terms: 14 + -5 = 9
9 + -4m = 4 + 3m + -16

Reorder the terms:
9 + -4m = 4 + -16 + 3m

Combine like terms: 4 + -16 = -12
9 + -4m = -12 + 3m

Solving
9 + -4m = -12 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
9 + -4m + -3m = -12 + 3m + -3m

Combine like terms: -4m + -3m = -7m
9 + -7m = -12 + 3m + -3m

Combine like terms: 3m + -3m = 0
9 + -7m = -12 + 0
9 + -7m = -12

Add '-9' to each side of the equation.
9 + -9 + -7m = -12 + -9

Combine like terms: 9 + -9 = 0
0 + -7m = -12 + -9
-7m = -12 + -9

Combine like terms: -12 + -9 = -21
-7m = -21

Divide each side by '-7'.
m = 3

Simplifying
m = 3

See similar equations:

| 5(3+z)-(8z+9)=-4z | | 2a-8a=-18 | | x^4-4x^3-4x^2+16x=0 | | 1-p-2=-9 | | K-(5-k)=3(k+8) | | 7r+4r=11 | | 6x+11=74-3x | | 6x+11=74-3 | | 9x+7=27+x | | (2c+3)(10c+1)= | | 5c-13=12 | | 8-4x-7x=19 | | (2a+5b)(a-b)= | | -8a+8a=-3 | | mn(m-6n)(m+n)= | | 6+7k-4=9 | | m-7m=143 | | (m-6n)(m+n)= | | M-8-2=.5(m-2) | | 5(x-10)=-20 | | 6t-5=4 | | 9d+8=13 | | 9k-2=43 | | 5+7k=21 | | 5a-6=16 | | 25.08+4k=80.06 | | 8x-4x-1=2 | | (w+9f)(w-2f)= | | (Y-8)-(y+4)=5y | | 2n-6=7n+5 | | (v+11)(v+3)= | | (v+11)(v-3)= |

Equations solver categories